Variable Amplitude Testing of 2024-T351 Aluminum Alloy Using Ultrasonic and Servo-hydraulic Fatigue Testing Equipment. (2015) - Fitzka, M.; Mayer, H.
Abstract: Ultrasonic fatigue testing allows time saving investigations up to the very high cycle fatigue regime. The high frequency and adapted testing method may influence measured fatigue properties. Servo-hydraulic and ultrasonic test data of 2024-T351 aluminum alloy show comparable lifetimes for constant amplitude tests at load ratio R=0.1 and R=0.5. In ultrasonic variable amplitude (VA) tests, amplitude is varied over successive pulses ("block loading") rather than cycles ("single-cycle loading"). Lifetimes agree for servo-hydraulic and ultrasonic VA block-loading tests at R=0.1. Considerably lower lifetimes measured in servo-hydraulic single-cycle tests suggest a pronounced influences of the loading sequence on VA fatigue damage.